2011
DOI: 10.1097/sap.0b013e3181f32319
|View full text |Cite
|
Sign up to set email alerts
|

The Extended Transverse Musculocutaneous Gracilis Flap

Abstract: The dimensions of a TMG flap can be increased horizontally (superoposterior thigh) as well as vertically. The vertical portion can be harvested either by undermining the skin inferior to the lower transverse skin incision or by raising a trilobed skin paddle to harvest even more tissue from the medial thigh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 25 publications
1
34
0
1
Order By: Relevance
“…19 However, as pointed out by Aly, 18 the limiting factor is often the quality of the thigh's superficial fascia rather than the superior attachment, and inferior descent may still result. The relative paucity of available volume may be improved by beveling the dissection through the fat, 6 shifting the dissection more posteriorly in the thigh, 14 or incorporation of a vertical limb into the flap design, creating a "trilobed" flap 7 or L-shaped flap. 20 These techniques effectively incorporate more of the thigh's adipose tissue and expand the utility of the flap to include moderate-sized breast reconstructions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…19 However, as pointed out by Aly, 18 the limiting factor is often the quality of the thigh's superficial fascia rather than the superior attachment, and inferior descent may still result. The relative paucity of available volume may be improved by beveling the dissection through the fat, 6 shifting the dissection more posteriorly in the thigh, 14 or incorporation of a vertical limb into the flap design, creating a "trilobed" flap 7 or L-shaped flap. 20 These techniques effectively incorporate more of the thigh's adipose tissue and expand the utility of the flap to include moderate-sized breast reconstructions.…”
Section: Discussionmentioning
confidence: 98%
“…The available volume for harvest has been increased by shifting the skin paddle posteriorly and beveling the dissection to include more of the deep adipose tissue. 6 In addition, the use of a combined transverse and vertical skin paddle has also been described as a means of increasing the flap volume. 7 Finally, the use of a vertical skin paddle has been reintroduced as a viable option in selected patients, potentially avoiding the problems of scar migration and labial spreading.…”
Section: Plastic and Reconstructive Surgery • September 2015mentioning
confidence: 99%
“…The TUG flap (also known as transverse musculocutaneous gracilis flap, TMG) has been considered by many authors as the second line treatment for autologous breast reconstruction in patients whom abdominal donor sites are unavailable, because of its constant and reliable anatomy that facilitates flap harvest (Huemer, Bauer, Wechselberger, & Schoeller, ; Schoeller, Meirer, Gurunluoglu, Piza‐Katzer, & Wechselberger, ) making it a preferred option for moderate sized breasts. (Schoeller et al, ; Wong, Mojallal, Bailey, Trussler, & Saint‐Cyr, ) Nevertheless, recent works have demonstrated that the PAP flap is becoming more popular as it has several advantages over the TUG flap such as a longer pedicle, higher tissue volume, no disruption of inguinal lymphatics, and low donor site morbidity (Hunter et al, ; Allen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons have always looked into ways of safely expanding skin paddle sizes; strategies such as L‐shaped and T‐shaped skin paddle designs and incorporation of a deeper layer of fat have been implemented with some success (Wong et al, ; Vega et al, ; Saint‐Cyr et al, ; Fattah, Figus, Mathur, & Ramakrishnan, ). However, theses attempts still inevitably led to increased complication rates when skin paddles were extended past the midline of the posterior thigh (Bodin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The pedicle enters the gracilis muscle between 8 and 12 cm below the pubic tubercle. The pedicle length is 6–8 cm . The average flap volume harvested reported is ∼350 mL …”
Section: Discussionmentioning
confidence: 99%